Joan : a novel - Chen, Katherine J., 1990- (Random House, 2022)
"1412. France is mired in a losing war against England. Its people are starving. Its king is in hiding. From this chaos emerges a teenage girl who will turn the tide of battle and lead the French to victory, an unlikely hero whose name will echo across the centuries. In Katherine J. Chen's hands, the myth and legend of Joan of Arc is transformed into a flesh-and-blood young woman: reckless, steel-willed, and brilliant. This stunningly-researched novel is a sweeping narrative of her life, from a childhood steeped in both joy and violence, to her meteoric rise to fame at the head of the French army, where she must navigate both the dangers of the battlefield and the equally treacherous politics of the royal court. For there are many who are threatened by a woman who leads, and Joan draws wrath and suspicion from all corners, even while her first tastes of fame, wealth, and glory leave her vulnerable to her own powerful ambition"--